Activation of the Tor/Myc signaling axis in intestinal stem and progenitor cells affects longevity, stress resistance and metabolism in drosophila - Strilbytska, Olha M.; Edgar, Bruce (Comparative biochemistry and physiology. B, Biochemistry & molecular biology, 2017)
The TOR (target of rapamycin) signaling pathway and the transcriptional factor Myc play important roles in growth control. Myc acts, in part, as a downstream target of TOR to regulate the activity and functioning of stem cells. Here we explore the role of TOR-Myc axis in stem and progenitor cells in the regulation of lifespan, stress resistance and metabolism in Drosophila. We found that both overexpression of rheb and myc-rheb in midgut stem and progenitor cells decreased the lifespan and starvation resistance of flies. TOR activation caused higher survival under malnutrition conditions. Furthermore, we demonstrate gut-specific activation of JAK/STAT and insulin signaling pathways to control gut integrity. Both genetic manipulations had an impact on carbohydrate metabolism and transcriptional levels of metabolic genes. Our findings indicate that activation of the TOR-Myc axis in midgut stem and progenitor cells influences a variety of traits in Drosophila.